2021
DOI: 10.3389/fnins.2020.604350
|View full text |Cite
|
Sign up to set email alerts
|

A Novel CCM2 Missense Variant Caused Cerebral Cavernous Malformations in a Chinese Family

Abstract: Cerebral cavernous malformations (CCMs) are common vascular malformations in the central nervous system. Familial CCMs (FCCMs) are autosomal dominant inherited disease with incomplete penetrance and variable symptoms. Mutations in the KRIT1, CCM2, and PDCD10 genes cause the development of FCCM. Approximately 476 mutations of three CCM-related genes have been reported, most of which were case reports, and lack of data in stable inheritance. In addition, only a small number of causative missense mutations had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…A retrieved result from Web of Science, PubMed, and Wanfang Data Knowledge Service Platform databases since 2000, with the terms familial cerebral cavernous malformations, mutation, and Chinese, articles published in English or Chinese with essential information about the mutations were included. We collected 24 pathogenetic alterations of fCCMs first identified in the Chinese population ( Chen et al, 2002 ; Xu et al, 2003 ; Mao et al, 2005 , 2016 ; Ji et al, 2006 ; Zhao et al, 2011 ; Wang et al, 2013 , 2017 , 2018 ; Zhu et al, 2014 ; Yang et al, 2017 ; Du et al, 2019 ; Han et al, 2020 ; Jiang et al, 2020 ; Yang L. et al, 2020 ; Yang Q. et al, 2020 ; Zhang et al, 2020 ; Liu et al, 2022 ). As exhibited in Table 3 , the majority (18/24) of Chinese fCCMs pathogenetic alterations are in KRIT1/CCM1 gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrieved result from Web of Science, PubMed, and Wanfang Data Knowledge Service Platform databases since 2000, with the terms familial cerebral cavernous malformations, mutation, and Chinese, articles published in English or Chinese with essential information about the mutations were included. We collected 24 pathogenetic alterations of fCCMs first identified in the Chinese population ( Chen et al, 2002 ; Xu et al, 2003 ; Mao et al, 2005 , 2016 ; Ji et al, 2006 ; Zhao et al, 2011 ; Wang et al, 2013 , 2017 , 2018 ; Zhu et al, 2014 ; Yang et al, 2017 ; Du et al, 2019 ; Han et al, 2020 ; Jiang et al, 2020 ; Yang L. et al, 2020 ; Yang Q. et al, 2020 ; Zhang et al, 2020 ; Liu et al, 2022 ). As exhibited in Table 3 , the majority (18/24) of Chinese fCCMs pathogenetic alterations are in KRIT1/CCM1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…The genomic DNA was extracted from each family member’s peripheral blood. DNA libraries were constructed and sequenced to a target depth of 100 × on the Illumina X-TEN platform, as previously reported ( Han et al, 2020 ). Reads were aligned to the reference genome (hg19) using BWA-MEM.…”
Section: Methodsmentioning
confidence: 99%
“…Although this work was primarily focused on the traditionally recognized PTB functional pocket, Core2, it provided the foundation for one of our protein structural simulation programs, probability density functions-based MODELLER [23], making our novel integrated in-silico/structural simulation analysis more thorough. Furthermore, recent efforts for in-silico analysis of Core1 in a genetic variant that is co-segregated in a large Chinese CCM pedigree [33] provide us with additional strong evidence for supporting this methodology. On the structural level, each amino acid substitution frequently resulted in perturbations within the tertiary structure of the PTB domain.…”
Section: Discussionmentioning
confidence: 96%
“…3, Supple Fig. 2A, Supple Video 3A, 3E) is a pathogenic mutation in the β2 strand (β-sheet 1), with minimal overlap between the amino acid side chains in both tertiary structure modalities [33]. There is misalignment in the β2, β2/3 loop, and α1/β2 loop between the two structures.…”
Section: Genomic Variants With Nssnps Only Have Local Effectsmentioning
confidence: 99%
“…A large autopsy study showed that the prevalence of CCM accounted for 0.1 to 0.5% of the total population ( 3 ), while other research has indicated that CCM influences ~10 to 20% of all cerebral vascular abnormalities ( 4 ). The disease can occur sporadically or by way of familial autosomal dominant inheritance without complete penetrance ( 5 ), with most cases having the former nature. The age of onset of CCM is typically 20 to 30 years of age or older.…”
Section: Introductionmentioning
confidence: 99%